The Potential of Trigona Honey as a Supplementary Therapy for Vascular Cognitive Impairment in Patients with Acute Ischaemic Stroke - Zarim, Mohd Haniff Abu; Ghazali, Anis Kausar; Abdul Halim, Sanihah; Abd Rahman, Engku Nur Syafirah Engku; A. Abusalah, Manal Abdel Haleem; Chan, Yean Yean; Hashim, Sabarisah; Hashim, Sabarisah (Malaysian Journal of Medical Sciences, 2025)
Background: Vascular cognitive impairment (VCI) is a common, yet often underrecognised, consequence of acute ischaemic stroke. Despite its prevalence, therapeutic strategies targeting VCI remain limited. Trigona honey, known for its antioxidant and neuroprotective properties, may offer a novel adjunctive intervention to improve cognitive outcomes after stroke. Methods: This randomised controlled study involved 48 patients diagnosed with acute ischaemic stroke. Participants were randomly assigned to two equal groups: an intervention group receiving daily supplementation with Trigona honey (n = 24) and a control group without supplementation (n = 24). Cognitive function was evaluated using the Montreal Cognitive Assessment (MOCA), and global disability was measured using the Modified Rankin Scale (MRS). Assessments were conducted at baseline and after three months of intervention. Results: At baseline, 66.7% of participants were male, with most exhibiting mild cognitive impairment. After three months, the intervention group showed significant improvement in MOCA scores (from 20.08 ± 4.53 to 24.33 ± 3.64), while the control group showed only a modest increase (from 18.42 ± 5.12 to 19.67 ± 6.31). The between-group difference in MOCA scores was 4.25 (95% CI: 3.07, 5.43; P < 0.001). Functional status also improved significantly in the Trigona honey group, with a mean change in MRS score of –1.29 (95% CI: –1.71, –0.87; P < 0.001), indicating enhanced independence compared to the control group. Conclusion: Trigona honey supplementation significantly improved cognitive performance and functional outcomes in patients with VCI following ischaemic stroke, supporting its role as a promising adjunct in stroke rehabilitation.